2006
DOI: 10.2337/diabetes.55.03.06.db05-0832
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-Proteasome System and Inflammatory Activity in Diabetic Atherosclerotic Plaques

Abstract: The role of ubiquitin-proteasome system in the accelerated atherosclerotic progression of diabetic patients is unclear. We evaluated ubiquitin-proteasome activity in carotid plaques of asymptomatic diabetic and nondiabetic patients, as well as the effect of rosiglitazone, a peroxisome proliferator-activated receptor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 42 publications
5
69
1
2
Order By: Relevance
“…It was reported that PSMA6 had a functional relation with LTA, 7 whose sequence variations were associated with the severity of atherosclerosis. 8 In addition, PSMA6 was reported to be involved in the diabetic atherosclerosis, 16 and the association of À8GG genotype with the thickness of intima-media in carotid artery was recently Table 2 Association between CAD and PSMA6 -8C4G (rs1048990) Figure 1 Meta-analysis of data from replication studies for the association between PSMA6 À8C4G and CAD. Odds ratio and 95% confidence interval (95% CI) are schematically indicated for each replication study.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that PSMA6 had a functional relation with LTA, 7 whose sequence variations were associated with the severity of atherosclerosis. 8 In addition, PSMA6 was reported to be involved in the diabetic atherosclerosis, 16 and the association of À8GG genotype with the thickness of intima-media in carotid artery was recently Table 2 Association between CAD and PSMA6 -8C4G (rs1048990) Figure 1 Meta-analysis of data from replication studies for the association between PSMA6 À8C4G and CAD. Odds ratio and 95% confidence interval (95% CI) are schematically indicated for each replication study.…”
Section: Resultsmentioning
confidence: 99%
“…We reported previously that oxidative stress-dependent UPS overactivity contributes to the clinical instability of atherosclerotic plaques in hypertensive, 15 diabetic, 16 and symptomatic patients 17 by promoting plaque rupture induced by NF-B-dependent inflammation. Now, in the present report, we provide evidence for the critical involvement of UPS in the process of plaque stabilization realized by HRT in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ can be activated by synthetic agonists belonging the family of thiazolidinediones, for instance rosiglitazone (RZ) (Mohanty et al, 2004). Recent studies performed in diabetic patients have shown that RZ reduces the inflammatory markers (Marfella et al, 2006), and it reduces blood pressure in hypertensive transgenic mice characterized by human renin and angiotensin overexpression (Ryan et al, 2004). These data suggest a protective role for PPAR␥ agonists in cardiovascular diseases because of their anti-inflammatory properties.…”
mentioning
confidence: 97%